Dari Kecemasan Menuju Kebahagiaan: Strategi Mengelola Respon Emosional dalam Kehidupan Sehari-Hari: Penelitian - Aris Mahfud; Salami Mahmud; Syatria Adymas Pranajaya; Restika Agustina; Maulidia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Anxiety is a common emotional response faced by many individuals in everyday life, especially due to academic, social, economic pressures, and uncertainty about the future. The purpose of this study is to identify effective strategies in managing anxiety and building happiness, identify factors that trigger anxiety, and provide practical guidance that can be applied by individuals and professionals in improving mental health. This study uses a library research method by reviewing various credible written sources such as books, scientific journals, and academic articles related to emotional regulation, anxiety, and happiness. The results of the study state that effective emotional management strategies include mindfulness practices to be present and accept current emotions without judgment, positive affirmations, optimistic mindsets, self-acceptance, social support, and developing a healthy lifestyle through exercise, adequate sleep, and regular eating patterns. The discussion shows that good emotional response management allows individuals to respond to anxiety reflectively and constructively so as to improve psychological well-being, productivity, and the quality of social relationships. These findings provide practical guidance for individuals, educators, counselors, and psychology practitioners in developing interventions that support long-term mental health and happiness.